Bank Competition and Bargaining over Refinancing - Emiris, Marina; Koulischer, François; Spaenjers, Christophe (The Review of Corporate Finance Studies, 2026)
Abstract We model mortgage refinancing as a bargaining game involving the borrowing household, the incumbent lender, and outside banks. We show that bargaining can provide a competitive advantage to the incumbent bank. In equilibrium, the borrower’s ability to refinance depends on the incumbent bank’s cost (dis)advantage relative to locally present competing banks and on the average creditworthiness of borrowers in the relevant market. It is also driven by borrower impatience and switching costs. We find empirical support for the key predictions of our model in an administrative data set covering the universe of mortgages in Belgium. (JEL G11, G21, G51)